Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/medu.13367
|View full text |Cite
|
Sign up to set email alerts
|

Exploring examinee behaviours as validity evidence for multiple-choice question examinations

Abstract: Our study provides some validity evidence that test-takers' descriptions of their cognitive processes during completion of high-quality clinical-vignette MCQs align with processes expected in real-world clinical reasoning. This supports one of the assumptions important for interpretations of MCQ examination scores as meaningful measures of clinical reasoning. Our observations also suggest that MCQs elicit other cognitive processes, including certain test-taking behaviours, that seem 'inauthentic' to real-world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…If the questions used in our study are representative of undergraduate medical curricula and average question difficulty, then cues provided in SBAs could impact on the validity of around a quarter of the examination. These items are assessing the candidate’s ability to use cues or engage in test-taking behaviours such as using the answer options to make deductions about the correct answer rather than using clinical reasoning, arriving at the correct answer by eliminating wrong SBA answer options8 and/or ‘best-guessing’ from the answers available. We have shown that VSAs mitigate this risk by removing the option menu and compelling candidates to determine the correct answer themselves based on the clinical information provided, which is more akin to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the questions used in our study are representative of undergraduate medical curricula and average question difficulty, then cues provided in SBAs could impact on the validity of around a quarter of the examination. These items are assessing the candidate’s ability to use cues or engage in test-taking behaviours such as using the answer options to make deductions about the correct answer rather than using clinical reasoning, arriving at the correct answer by eliminating wrong SBA answer options8 and/or ‘best-guessing’ from the answers available. We have shown that VSAs mitigate this risk by removing the option menu and compelling candidates to determine the correct answer themselves based on the clinical information provided, which is more akin to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Because patients do not present with a list of five possible diagnoses, investigations or treatment options,8 SBA questions do not simulate the ‘situations they [the candidates] will face when they undertake patient-related clinical tasks’ (p66) 9. Any alternative method of assessing applied medical knowledge must therefore provide increased content and response process validity, without resulting in significant reductions in other types of validity, reliability, acceptability, educational impact or an unacceptable increase in cost 10.…”
Section: Introductionmentioning
confidence: 99%
“…To better fill this gap in our understanding, more robust means of detecting error in clinical practice [ 5 ] and novel experimental approaches are necessary. We believe using multiple-choice questions (MCQs), widely applied in standardized exams to assess clinical reasoning and found to elicit real-world reasoning processes in previous research [ 26 28 ], supplemented with a think aloud (TA) protocol can provide valuable insight into such errors. Furthermore, MCQs hold the advantage of having an a priori distinct correct answer, allowing for a clear, prospective analysis that limits hindsight bias.…”
Section: Introductionmentioning
confidence: 99%
“…46 Even when MCQs replicate complex thought processes such as clinical reasoning, learners still engage in strategies of looking for clues in the question and formatting to help them find the answers. 49 MCQs can be used for retrieval practice but should be used with care. Other test formats may better accomplish educators' aims.…”
Section: Test Formatmentioning
confidence: 99%